Malcolm X - Yasin, Khalid; One Islam Productions (N.S. W, Australia : One Islam Productions, 2006)
Forty years after the death of Malcom X, his righteous influence is still motivating and influencing individuals all around the world in their fight for their human rights. In this lecture, Khalid Yasin sheds some lights on the life of Al-Hajj Malik Al-Shabbaz, better known to the world as Malcolm X
Title from title screen
Lecturer : Khalid Yasin
Keywords: X, Malcolm, -- 1925-1965; African American Muslims -- Biography; African Americans -- Race identity